Molecular diagnosis: an alternative for the detection of pathogens in food - Eliana Ximena Urbano Cáceres; Carlos Alexander Huertas Caro; María Inés Torres Caycedo (Universidad de Ciencias Médicas de La Habana, 2019)
Introduction: Foodborne diseases constitute a health problem in the world, involving products of animal origin, vegetables, water sources, and foods ready for consumption.  The problem arises because of the inadequate manipulation of food and the possibility of transmission of pathogenic microorganisms, mainly of a bacterial type. Objective: To describe the different conventional and molecular diagnostic techniques used in the food industry. Material and Methods: A search was carried though the analysis of review articles, original articles, and theses during a period of three months; these articles were written in English, Portuguese and Spanish.  In their content, they demonstrated the use of conventional and molecular methodology for the identification of microorganisms in different types of food. Results: The conventional methods for the identification of these microorganisms make use of well-established protocols and norms, but require too much time for their identification and, in some cases, they provide low sensitivity and specificity. Molecular techniques are proposed as an alternative for the microbiological evaluation of food because they are fast, sensitive and reliable. Conclusions: Molecular techniques are proposed as a new and faster alternative for the detection of microorganisms, reducing the time for the emission of results from days to hours; identifying pathogenesis factors, virulence and drug resistance with only one assemblage, thus providing high sensitivity and specificity. Keywords: Pathogen, Diseases, Food, Transmission, Molecular Diagnostic Techniques.